2021
DOI: 10.1111/tme.12801
|View full text |Cite
|
Sign up to set email alerts
|

Pain control and functional improvement in patients treated by autologous conditioned serum after failure of platelet rich plasma treatments in knee osteoarthritis

Abstract: Objective To assess the efficacy of autologous conditioned serum (ACS) for the treatment of patients with knee osteoarthritis after failure of medical treatments and platelet rich plasma (PRP) injections. Background Knee osteoarthritis is the most common form of arthritis. Prior to prosthetic surgery these patients might benefit from medical treatments, physiotherapy, and in case of their ineffectiveness, from autologous blood component injections. Methodology We have treated 30 patients with Kellgren‐Lawrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…While the data of contents indicated that PRP had lower levels of IL-1Ra and may limit its ability for pain relief, it further highlights the role of IL-1Ra in the treatment of knee OA. Leone et al [ 47 ] reported that ACS treatment responders had significantly higher levels of IL-1Ra levels than non-responders, with average concentrations of 930 and 200 pg/mL, respectively. This result is consistent with the present one, while the mean IL-1Ra concentration of PRP and ACS 3 h were 157.9 and 902.9 pg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the data of contents indicated that PRP had lower levels of IL-1Ra and may limit its ability for pain relief, it further highlights the role of IL-1Ra in the treatment of knee OA. Leone et al [ 47 ] reported that ACS treatment responders had significantly higher levels of IL-1Ra levels than non-responders, with average concentrations of 930 and 200 pg/mL, respectively. This result is consistent with the present one, while the mean IL-1Ra concentration of PRP and ACS 3 h were 157.9 and 902.9 pg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the present one, while the mean IL-1Ra concentration of PRP and ACS 3 h were 157.9 and 902.9 pg/mL, respectively. It is interesting to note that Leone et al demonstrated that in patients with knee OA who had failed to prior PRP treatment, the response rate of ACS was 67% [ 47 ]. This is consistent with the results of the present study that ACS has a better efficacy on pain relief compared to PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ACS is becoming important in terms of reducing drug side effects and costs. It has been reported in studies that ACS therapy is successful in the treatment of knee OA [ 7 , 8 , 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, showed higher pain reduction and functional improvement with ACS compared to PRP, likely due to the higher IL-1Ra levels, decrease in IL-1β and improved synovial fluid viscosity [145,146]. Furthermore, it has been found that 67% of subjects with painful knee OA who had failed previous standard therapy, including physiotherapy and PRP, had a reduction of pain assessed on VAS one month after administration of ACS and this result persisted at 6 and 12 months of follow-up [147]. A notable finding from this study was that responders had significantly higher levels of IL-1Ra in their ACS compared to non-responders, underscoring the potential benefits of intra-articular IL-1β blockade in knee OA [147].…”
Section: Knee Osteoarthritis Subtype Representative Moleculesmentioning
confidence: 97%
“…Furthermore, it has been found that 67% of subjects with painful knee OA who had failed previous standard therapy, including physiotherapy and PRP, had a reduction of pain assessed on VAS one month after administration of ACS and this result persisted at 6 and 12 months of follow-up [147]. A notable finding from this study was that responders had significantly higher levels of IL-1Ra in their ACS compared to non-responders, underscoring the potential benefits of intra-articular IL-1β blockade in knee OA [147]. These reports suggest that anti-cytokine therapy could have potential benefits in obesity-related knee OA considering their role in maintaining the low-grade inflammatory state characteristic of obesity, however they are yet to be studied in such conditions.…”
Section: Knee Osteoarthritis Subtype Representative Moleculesmentioning
confidence: 99%